Equi-protein Replacement of Fishmeal with Leucaena Leaf Protein Concentrate: An Assessment of Performance Characteristics and Muscle Development in the Chicken - Agbede, Johnson O. (International Journal of Poultry Science, 2003)
A batch of three hundred 7- day old Shaver broiler-chicks was used to assess the equi-protein replacement of fishmeal (FM) protein with Leucaena leaf protein concentrates (LLPC) in broiler-starter mash. Before the feeding trial, the LLPC was analyzed for its protein, amino acids, phytin and tannin contents. Thereafter, five diets were tested. The control (diet 1) had 5% FM protein whose protein was gradually replaced at 25, 50, 75 or 100% with LLPC in diets 2 to 5. Thus the inclusion level of LLPC was 2.24, 4.48, 6.72 or 8.96%, respectively for diets 2 to 5. The chicks were randomly assigned in triplicate of 60 chicks per dietary treatment. The average weight gain (AWG), average feed consumption (AFC) and feed conversion ratio (FCR) of chicks fed the control diet were significantly (P